2021
DOI: 10.1130/g49097.1
|View full text |Cite
|
Sign up to set email alerts
|

Serpentinized peridotite versus thick mafic crust at the Romanche oceanic transform fault

Abstract: The crust beneath transform faults at slow-spreading ridges has been considered to be thin, comprising a thin mafic layer overlying serpentinized peridotite. Using wide-angle seismic data, we report the presence of a Moho at ~6 km depth and a low-velocity anomaly extending down to 9 km beneath the 20-km-wide Romanche transform valley floor in the equatorial Atlantic Ocean. The low crustal velocities above the Moho could be due to either highly serpentinized mantle peridotite or fractured mafic rocks. The exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 33 publications
5
26
0
Order By: Relevance
“…Therefore, most observed crustal thickness estimates compare well to predictions from petrological models, suggesting an average crustal thickness of 6 km emplaced at a normal mantle temperature of 1,300°C (e.g., Korenaga et al, 2002;McKenzie & Bickle, 1988). However, slightly reduced crustal thickness in the equatorial Atlantic of ∼5.3 km between Chain and Romanche, roughly 6 km north of Romanche (Gregory et al, 2021) and <5.5 km along our longitudinal profile may supports a cooler mantle underlying the equatorial Atlantic. This interpretation is supported by the exceptionally low degree of melting of the upper mantle in the equatorial Atlantic as indicated by the chemical composition of mantle-derived mid-ocean ridge peridotites and basalts (Bonatti et al, 1993;Dalton et al, 2014) and upper mantle S-wave velocity (Grevemeyer, 2020;James et al, 2014).…”
Section: Crustal Thickness As a Function Of Distance Across St Paul F...supporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, most observed crustal thickness estimates compare well to predictions from petrological models, suggesting an average crustal thickness of 6 km emplaced at a normal mantle temperature of 1,300°C (e.g., Korenaga et al, 2002;McKenzie & Bickle, 1988). However, slightly reduced crustal thickness in the equatorial Atlantic of ∼5.3 km between Chain and Romanche, roughly 6 km north of Romanche (Gregory et al, 2021) and <5.5 km along our longitudinal profile may supports a cooler mantle underlying the equatorial Atlantic. This interpretation is supported by the exceptionally low degree of melting of the upper mantle in the equatorial Atlantic as indicated by the chemical composition of mantle-derived mid-ocean ridge peridotites and basalts (Bonatti et al, 1993;Dalton et al, 2014) and upper mantle S-wave velocity (Grevemeyer, 2020;James et al, 2014).…”
Section: Crustal Thickness As a Function Of Distance Across St Paul F...supporting
confidence: 74%
“…in 2018. The profile is in total 850 km‐long, crossing farther south the Romanche transform fault (∼0°N) (Gregory et al., 2021) and the Chain fracture zone (∼2°S; Marjanović et al., 2020). Here, we use the data from the northernmost 350 km of the line containing 15 4‐component OBS with an average instrument spacing of 14.2 km.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…Previous studies have suggested that the region around the eastern ridge-transform intersection (RTI) of the Romanche TF is cold and displays an extremely thin crust 11 . However, recent seismic studies suggested that the crust is 5.5-6.5 km thick at the Romanche TF 5 , and the LAB lies at ~72 km depth beneath the 40 Myr-old lithosphere north of the transform 12 , arguing for the presence of a normal lithosphere in this region.…”
Section: Seismic Velocity Structure Of the Romanche Transform Faultmentioning
confidence: 97%
“…Away from active transform boundaries, the oceanic TFs are preserved as fracture zones (FZs), which extend over entire ocean basins and form some of the most prominent and continuous features on the ocean floor. The crustal structure of a few oceanic TFs has been studied through geophysical surveys 4 , 5 , but the properties and nature of the deep lithosphere and the lithosphere-asthenosphere boundary (LAB) at TFs remain enigmatic. Here, we present the velocity structure of the lithosphere at the Romanche TF down to 60 km depth below sea level (bsl).…”
mentioning
confidence: 99%
“…However, due to the low water solubility of olivine under topmost asthenosphere conditions (Fei & Katsura, 2020) and as discussed in the previous section, an even weaker mantle solely from an elevated water content is rather questionable. Furthermore, the reaction of seawater with peridotite can cause extensive serpentinization (e.g., Schroeder et al., 2002), such as observed down to 9 km beneath a thin mafic layer on Romanche OTF at equatorial Mid‐Atlantic Ridge (Gregory et al., 2021). The deformation mechanism of serpentinite may still favor stable sliding or localized faulting at the top mantle condition (Chernak & Hirth, 2010; Cox et al., 2021).…”
Section: Discussionmentioning
confidence: 99%